Emotional schemas in relation to educators’ social and emotional competencies to promote student SEL - Patricia A. Jennings; Pilar Alamos; Rebecca N. Baelen; Lieny Jeon; Pamela Y. Nicholas-Hoff (Social and Emotional Learning: Research, Practice, and Policy)
A rapidly growing body of research examines the social and emotional competencies (SEC) educators need to fulfill their professional roles effectively. The prosocial classroom model emphasizes the significance of educators' SECs in maintaining wellbeing, managing classrooms, building positive student relationships, and delivering proficient social-emotional learning (SEL) instruction. This paper examines the relationship between emotional schemas and educators’ SEC, exploring their relevance in understanding developmental contexts for both educators and students. Effective SEL instruction requires educators to model the skills they teach, manage stress and emotional reactivity, and provide “co-regulation” to help students manage their emotions. Despite the importance of these competencies, research has yet to fully clarify the constructs contributing to educators' SECs and how cultural variations in emotion understanding affect this dynamic. Emotional schemas, formed through developmental processes and socialization, influence psychological well-being, impact relationships, and can be adaptive or maladaptive. Theories of meta-emotion and metacognition provide frameworks for understanding and developing adapticas, their wellbeing, and their capacity to create prosocial classroom environments. We examine existing intervention strategies that support adaptive emotional schemas, aiming to improve educators' SECs, SEL instruction, and overall well-being. Finally, we propose directions for future research to enhance understanding and practical applications in educational settings. Impact Statement: We review and apply research based in metacognitive and metaemotion theories to understanding educators’ emotional schemas and how they may impact their capacity to cultivate and maintain socially and emotionally supportive environments and effectively promote students’ social and emotional learning (SEL). Through this lens, existing intervention strategies are reviewed and ideas for new and innovative intervention approaches are suggested. Implications for culturally responsive approaches are highlighted along with implications for enhancing educators’ commitment to diversity, equity, and inclusion.